Investigation on Antimicrobial Activity of Nickel(II) and Zinc(II) Complexes with Schiff Base Derived from Aminoacid Valine With Citral: Synthesis, Spectroscopic Analysis - Bencela, M.; Kumari, S. Sudha; Parmila, T.S. (International Journal of Scientific Research in Biological Sciences, 2019)
Ni(II) and Zn(II) metal complexes with Schiff base derived from Citral and Valine are synthesised and characterized on the basis of spectroscopic techniques (FT-IR, and UV-Visible) and magnetic susceptibility studies The IR spectral data indicated that the Schiff base coordinated to central Ni(II) and Zn(II) ions in a bridged-tridentate and bidentate fashion respectively. Magnetic moment and spectral studies suggest distorted octahedral around the Ni(II) ion and tetrahedral geomtry around Zn(II) ion. The preliminary antimicrobial activity has been evaluated against two Gram-negative bacteria; namely, Pseudomonas aeroginosa and Escherichia coli, one gram-positive bacteria Staphylococcus aureus, and antifungal activity are tested against Aspergillus sps and Candida albicans using disc diffusion method. The result revealed that Ni(II) complex exhibited potent activity when compared to Zn(II) complex and Schiff base.